RISKY BUSINESS: AN EXAMINATION OF DRINKING GAMES IN COLLEGE SETTINGS AND THEIR IMPACT: A SYSTEMATIC REVIEW - de Santana, Guilherme Farias; castaldelli-Maia, João Mauricio (Anais Eventos, 2025)
This systematic review explores the prevalence and impact of Drinking Games (DG) among college students. DGs involve social drinking with the goal of heavy alcohol consumption and are associated with risky behaviours. the review aims to quantify the relationship between DG participation, alcohol consumption, and negative outcomes. it also investigates gender moderation and unexplored motivational factors for DG engagement. Following PRiSMA guidelines, 34 studies were included after screening 317 records. the studies comprised n = 34,197 participants and were analysed for various variables, including gender dynamics, motivations, and associated negative consequences. Gender convergence in DG participation was noted, emphasizing the importance of gender-specific interventions. Participants were aware of risks but often perceived negative outcomes as a badge of honour. Motivations for DGs were linked to social interaction and a sense of belonging. Personality traits like sensation seeking and identification with college drinking culture played significant roles in DG engagement and outcomes. the review underscores the need for targeted interventions to address shifting perceptions of negative consequences and consider personality traits when designing preventive measures. it also highlights the significance of gender-specific strategies. However, variations in DG measurement and possible selection bias among heavy drinkers participating in DGs remain limitations. this systematic review provides insights into DG prevalence and its link to negative outcomes among college students. the findings stress the importance of tailored interventions and further research to mitigate risk factors and promote healthier drinking behaviours in this demographic.